Molecular signatures of endodontitis and pulpal inflammation: a comprehensive gene expression and multi-parameter analysis using GSE77459 microarray data: Molecular signatures of pulpal inflammation - Boreak, Nezar (Cellular and Molecular Biology, 2025)
Pulpal inflammation remains a significant endodontic challenge requiring improved molecular understanding for effective diagnosis and treatment. Current diagnostic methods largely depend on clinical assessments, necessitating molecular-level insights. This study aimed to analyze comprehensive gene expression profiles in pulpitis to identify potential diagnostic markers and understand underlying molecular mechanisms. We analyzed the GSE77459 dataset from Gene Expression Omnibus, comprising twelve pulpal tissue samples (six irreversible pulpitis and six normal controls). Gene expression profiling was performed using Affymetrix GeneTitan Multichannel Instrument. Pain assessment utilized visual analog scale (VAS) readings, with values >30mm indicating moderate to severe pain. Differential gene expression analysis was conducted using GEO2R, implementing a false discovery rate of 5%. Statistical significance was evaluated through adjusted p-values, log2 fold changes, and comprehensive visualization techniques including Volcano plots, Mean-Difference plots, and UMAP analysis. The analysis identified significant expression changes between inflamed and normal pulp tissues. Three genes showed notable upregulation: SNORD113-3 (log2FC: +0.71), RN5S290 (log2FC: +0.70), and SH3GL2 (log2FC: +0.67). Key downregulated genes included IGHV3-72 (log2FC: -1.66), IGKV1-5 (log2FC: -1.57), and IGHD (log2FC: -1.57). UMAP analysis revealed distinct clustering patterns between disease and control samples, while maintaining proximal positioning, indicating subtle yet consistent transcriptional differences. Statistical analysis showed that 62% of differentially expressed genes had significant adjusted p-values (<1e-8), with 25% exhibiting absolute log2FC values >1.2. This study reveals specific molecular signatures associated with pulpal inflammation, particularly highlighting the downregulation of immunoglobulin-related genes and upregulation of RNA processing factors. These findings provide potential molecular markers for pulpitis diagnosis and suggest new directions for therapeutic interventions in endodontic treatment.